Chemical composition and rumen degradability of forages and browse for goats and sheep in Sarawak. - Andrew Alek, Tuen; A., Djajanegara; A., Sukmawati (1994)
Fresh samples of 8 forages (Ischaemum magnum, Setaria kazungula [S. sphacelata var. sericea cv. Kazungula], Brachiaria decumbens, Calopogonium mucunoides, Pueraria phaseoloides, Stylosanthes gracilis [S. guianensis], Centrosema pubescens, Asystasia intrusa) and 6 browse species (Acacia mangium, Leucaena leucocephala, Gliricidia sepium, Artocarpus heterophyllus, Artocarpus integer, Manihot esculenta) were dried, ground and analysed for nitrogen, ash and mineral content. Degradability was determined by the nylon bag technique for 48 hours in the rumens of 3 fistulated goats and sheep fed on a diet of Pennisetum purpureum (19 g N/kg DM, DM degradability 72%) and soyabean meal. With the exception of phosphorus in Acacia mangium (0.9 g/kg DM) none of the minerals was considered deficient with respect to maintenance requirements. DM degradability of forage ranged from 58.3% (Centrosema pubescens) to 91.1% (Asystasia intrusa) while that of browse ranged from 33.6% (Acacia mangium) to 78.6% (Artocarpus heterophyllus). Sheep degraded Pueraria phaseoloides, Brachiaria decumbens, Artocarpus beterophyllus and Manihot esculenta significantly better (by 4-5%) than goats. It is concluded that browse species such as Artocarpus spp., Manihot esculenta and forages such as Ischaemum magnum and Asystasia intrusa have high nutritional values and offer considerable potential for selective utilization by ruminant livestock in Sarawak.